Volume of Hill Estimation for Engineering Earth Work - Nordianah Jusoh; Noorzalianee Ghazali; Siti Hafawati Jamaluddin; Siti Nor Nadrah Muhamad; Wan Juliyana Wan Ibrahim; Jamaludin Md. Ali; Wan Mohd Zulkifle Wan Yaacob (Journal of Computing Research and Innovation, 2018)
This study centralizes on the development of volume estimation calculation platform for earth engineering work. Estimation and comparison were done by using Foresight Civil Design and Survey (CDS) and Mathematica 7.0 software. Currently, Land Surveying companies are using Foresight Civil Design and Survey (CDS) software for its speed and automation. There are two methods used in Mathematica 7.0, which are Rational Quadratic Bezier Curve and Rational Cubic Bezier Curve. From this research, Rational Cubic Bezier Curve show its total hill measurement (volume) is nearer to value using Foresight Civil Design and Survey (CDS) software. Therefore, the Rational Cubic Bezier Curve is an alternative method to estimate the volume of the hill. The discrepancy between Rational Cubic Bezier Curve and Foresight Civil Design and Survey (CDS) mainly caused by curve tolerance has been generalized in Rational Cubic Bezier Curve.